A platinum complex that binds non-covalently to DNA and induces cell death via a different mechanism than cisplatin - Suntharalingam, Kogularamanan; Mendoza, Oscar; Duarte, Alexandra A; Mann, David J; Vilar, Ramon (Metallomics, 2013)
Cisplatin and some of its derivatives have been shown to be very successful anticancer agents. Their main mode of action has been proposed to be via covalent binding to DNA. However, one of the limitations of these drugs is their poor activity against some tumours due to intrinsic or acquired resistance. Therefore, there is interest in developing complexes with different binding modes and mode of action. Herein we present a novel platinum(ii)-terpyridine complex (1) which interacts non-covalently with DNA and induces cell death via a different mechanism than cisplatin. The interaction of this complex with DNA was studied by UV/Vis spectroscopic titrations, fluorescent indicator displacement (FID) assays and circular dichroism (CD) titrations. In addition, computational docking studies were carried out with the aim of establishing the complex's binding mode. These experimental and computational studies showed the complex to have an affinity constant for DNA of ∼10(4) M(-1), a theoretical free energy of binding of -10.83 kcal mol(-1) and selectivity for the minor groove of DNA. Long-term studies indicated that 1 did not covalently bind (or nick) DNA. The cancer cell antiproliferative properties of this platinum(ii) complex were probed in vitro against human and murine cell lines. Encouragingly the platinum(ii) complex displayed selective toxicity for the cancerous (U2OS and SH-SY5Y) and proliferating NIH 3T3 cell lines. Further cell based studies were carried out to establish the mode of action. Cellular uptake studies demonstrated that the complex is able to penetrate the cell membrane and localize to the nucleus, implying that genomic DNA could be a cellular target. Detailed immunoblotting studies in combination with DNA-flow cytometry showed that the platinum(ii) complex induced cell death in a manner consistent with necrosis.